2018
DOI: 10.1002/phar.2121
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Cardiovascular Risk Related to Individual Antimuscarinic Drugs Used to Treat Overactive Bladder: A UK Cohort Study

Abstract: BackgroundBlocking muscarinic receptors could have an effect on cardiac function, especially among elderly patients with overactive bladder (OAB).Study ObjectiveTo investigate the risk of cardiovascular (CV) events in users of antimuscarinic drugs to treat OAB.Design, Setting, and ParticipantsCohort study of new users of darifenacin, fesoterodine, oxybutynin, solifenacin, tolterodine, or trospium, 18 years or older, in the United Kingdom's Clinical Practice Research Datalink (CPRD), 2004–2012.Outcome Measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 32 publications
0
18
1
Order By: Relevance
“…This validation study was conducted in a population of patients treated for overactive bladder because this validation effort was part of a broader study on the safety of antimuscarinic drugs. 8,9,15 We do not expect that these CV outcomes and risk factors would be better or less well recorded among these patients than in the general population. Furthermore, CV risk factors investigated here might have been recorded in patients' electronic records before treatment started.…”
Section: Part 2 Understanding Outcome Misclassificationmentioning
confidence: 87%
See 2 more Smart Citations
“…This validation study was conducted in a population of patients treated for overactive bladder because this validation effort was part of a broader study on the safety of antimuscarinic drugs. 8,9,15 We do not expect that these CV outcomes and risk factors would be better or less well recorded among these patients than in the general population. Furthermore, CV risk factors investigated here might have been recorded in patients' electronic records before treatment started.…”
Section: Part 2 Understanding Outcome Misclassificationmentioning
confidence: 87%
“…This study was the validation component of a drug safety study 8 ("parent study") that included patients aged ≥18 years who were continuously enrolled in the UK CPRD primary care database (GOLD) for ≥12 months and were newly exposed to antimuscarinic medications to treat overactive bladder (darifenacin, fesoterodine, oxybutynin, solifenacin, tolterodine, or trospium) in 2004 to 2012. Patients with a diagnosis of cancer other than nonmelanoma skin cancer were excluded, as were HIV+ patients because their health service utilization might not be fully captured.…”
Section: Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Medications with strong anticholinergic properties such as antimuscarinics have been associated with cognitive and other adverse effects including risk of mortality in diverse samples of older adults [14][15][16][17][18][19][20][21][22][23][24][25] . Two recent studies have evaluated the risk of cardiovascular events and overall mortality with antimuscarinics and provided conflicting findings 26,27 . Arana et al found increased risk of cardiovascular events and mortality among adults using oxybutynin compared to tolterodine 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Two recent studies have evaluated the risk of cardiovascular events and overall mortality with antimuscarinics and provided conflicting findings 26,27 . Arana et al found increased risk of cardiovascular events and mortality among adults using oxybutynin compared to tolterodine 26 . However, Margulis et al found no differential risk of cardiovascular events and overall mortality among adults using antimuscarinic agents for OAB 27 .…”
Section: Introductionmentioning
confidence: 99%